Konsep Dosa dalam Perjanjian Lama dan Hubungannya dengan Konsep Perjanjian Menurut Kejadian 3:1-24 - Jenita Bora; Ailin Triwungsu; Malik Bambangan (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
This article discusses the relationship between the concept of sin in the Old Testament and the concept of the covenant. The thesis of this article is that the concept of sin in the Old Testament is describing the side of God's attribute, namely God's justice. While the concept of the covenant (covenant) is describing the attributes of God that represent God's love. The concept of sin in the Old Testament and its consequences is not showing God's wrath that is contrary to the God of love, but rather describing a God who is just and sovereign over His laws. Likewise, the concept of the covenant that is describing God's love, where God initiated the first and reminded Himself to humans who are His creations in the covenant. This agreement also shows God's loyalty to His people. This article will show that both the concept of sin in the Old Testament and the Testament concept have close ties and are bound together. By conducting the literature study method, this article will contribute conceptually useful to the concept of sin in the Old Testament and also the concept of the Covenant.